PERBANDINGAN PEMBERIAN LIDOKAIN 2% INTRAVENA DENGAN FENTANIL INTRAVENA SETELAH ANESTESI UMUM DIHENTIKAN TERHADAP KEJADIAN BATUK SAAT EKSTUBASI SADAR - Gunawan, Dedy Hendra (Universitas Tribhuwana Tunggadewi, 2020)
Cough after extubation not only causes patient discomfort, but can also cause hypertension, tachycardia, increased intracranial, intraocular, and intra-abdominal pressure, which can cause coronary ischemia, arrhythmia, or surgical difficulties. Cough after extubation can be prevented with several drugs. The purpose of this study is to compare the effects of lidocaine 2% 1.5 mg / kg intravenously compared to fentanyl 1 mcg / kg intravenously in reducing the incidence of cough during conscious extubation. Research conducted on 36 patients aged 18-65 years with the physical status of the American Society of Anesthesiologists (ASA) I and II who performed operations with general anesthesia using oral intubation in a position during supine surgery and correctly extubated. Patients were divided into 2 groups: group A received fentanyl 1 mcg / kg and group B received lidocaine 2% 1.5 mg / kg. The results of the study concluded that 2% lidocaine at a dose of 1.5 mg / kg better in coughing and rejected haemodynamics compared to fentanyl at a dose of 1 mcg / kg at the time of extubation was understood to be moderate.